Grandmaternal investment and early childhood injury: the role of X-chromosomal relatedness - Tanskanen Antti; Danielsbacka Mirkka (Cambridge University Press, 2025)
Evolutionary theory posits that grandmothers can increase their inclusive fitness by investing time and resources in their grandchildren. According on the X-linked grandmother hypothesis, the asymmetric inheritance of X-chromosomes should be responsible for the biased effect of the investment by maternal and paternal grandmothers towards granddaughters and grandsons. The British Millennium Cohort Study (n=4445 children) was used to investigate the association between grandmaternal childcare and children's injuries between the ages of 9 months and 3 years. Support was found for the X-linked grandmother hypothesis predicting that the investment of paternal grandmothers benefits more granddaughters than grandsons, the investment of paternal grandmothers benefits granddaughters more than the investment of maternal grandmothers, and the investment of maternal grandmothers is similarly associated with the injuries of granddaughters and grandsons. However, no support was found for the prediction that maternal grandmothers benefit more grandsons than paternal grandmothers. Thus, some, although not univocal, evidence for the prediction that X-chromosomal relatedness shapes the grandmaternal effect on child outcomes was found.